Evolving Strategies to Eliminate the CD4 T Cells HIV Viral Reservoir via CAR T Cell Immunotherapy - York, Jarrod; Gowrishankar, Kavitha; Micklethwaite, Kenneth; Palmer, Sarah; Cunningham, Anthony L.; Nasr, Najla (Frontiers in Immunology, 2022)
Although the advent of ART has significantly reduced the morbidity and mortality associated with HIV infection, the stable pool of HIV in latently infected cells requires lifelong treatment adherence, with the cessation of ART resulting in rapid reactivation of the virus and productive HIV infection. Therefore, these few cells containing replication-competent HIV, known as the latent HIV reservoir, act as the main barrier to immune clearance and HIV cure. While several strategies involving HIV silencing or its reactivation in latently infected cells for elimination by immune responses have been explored, exciting cell based immune therapies involving genetically engineered T cells expressing synthetic chimeric receptors (CAR T cells) are highly appealing and promising. CAR T cells in contrast to endogenous cytotoxic T cells can function independently of MHC-I to target HIV-infected cells, are efficacious and have demonstrated acceptable safety profiles and long term persistence in peripheral blood. In this review, we present a comprehensive picture of the current efforts to target the HIV latent reservoir, with a focus on CAR T cell therapies. We highlight the current challenges and advances in this field, while discussing the importance of novel CAR designs in the efforts to find a HIV cure.